POTENTIOMETRIC STUDY OF MIXED LIGAND COMPLEXES OF PROPIOPHENONE DERIVATIVES WITH TRANSITION METAL AND AMINO ACIDS. - M.B., SWAMI (Innovare Journal of Sciences, 2020)
Objective: Mixed ligand complexes plays an important role in numerous chemical and biological systems 1-2 Like water softening, ion exchange resins, electroplating, dyeing antioxidants, photosynthesis in plants, removal of undesirable and harmful metals from living organisms etc. mixed co-ordination by proteins and related substances has been subject of the investigation of many workers. Material and Methods: Simple and Halogen substituted phenols are starting materials for preparation of primary ligands and were prepared by Fries-migration reactions. Primary ligands are i) 3-chloro, 2-hydroxy-propiophenone[L1], 2) 2-Hydroxy propiophenone [L4] all these ligands are characterized by I.R. spectra I .R bands of the ligands in KBr phase ,[>C=O and –OH groups were identified ] due to >C=O group at (1650-1670) . And –OH group at (3650-3531) and its purity are checked by T.L.C., M.P. and organic tests. The proton-ligand & metal-ligand stability constant of binary and ternary systems of Cu(II) with propiophenone derivatives and amino acids have been studied potentiometrically by Irving-Rossotti technique in 60% (v/v) Ethanol Water medium at 250c ± 0.10c and at constant 0.1M Tonic strength. The difference between the stability of ternary and their corresponding binary complexes has been expressed interms of parameter logk and negative logk values suggest that the formation of ternary complexes are favorable and variation of logK have been explained interms metal-ligand( pi) interaction, size of chelating ring and Steric factors. Results: The stability constant of bivalent metal complexes derived from similar type of ligands generally follow the Irving Williams order. The present complexes follow the order of stability as L1 = Mn > Cu > Zn > Ni> Co. And L2 = Cu > Ni > Co > Zn > Mn. The order of stability of ternary complexes with respect to secondary ligands for respective primary ligands is. L1=L - Phala > L - pro > L - Thre > Gly. L2=L - Pro > L - phala > Gly > L - Thre Conclusion: In the present investigation, all these complex systems contains five membered ring on the one side with amino-acids. And six member ring on other side with primary ligand.